Freeze drying under vacuum assisted synthesis of LiFePO4@MWCNTs composite with phytic acid as phosphorus source for advanced Li-storage. (November 2021) - Li, Yin; Wang, Li; Zhang, Hui; Liang, Feng; Yao, Yaochun; Zhang, Keyu
Abstract: Three-dimensional (3D) LiFePO4 @MWCNTs composite has been prepared using phytic acid as the phosphorus source by a simple solvothermal method combined with freeze drying under vacuum. The relationships between the phase structures, the morphologies and electrochemical performance characteristics of the as-prepared samples are studied using a series of characterization methods. It is found that the MWCNTs wrap around the LiFePO4 particles to form a 3D network because of the reactions between the special functional groups of the phytic acid with Fe 2+ and –CO or –COOH on the surface of the functionalized MWCNTs, resulting in the improvement of conductivity and the electron and ion transport. Due to these merits of MWCNTs and phytic acid, the LiFePO4 @MWCNTs exhibits good electrochemical performance with high initial discharge capacities of 152.7, 149.6 and 138.8 mAh g −1 at 1, 2 and 5C, respectively. Even at 10C, it still delivers a capacity of 117.5 mAh g −1 . Highlights: LFP@MWCNTs nanocomposite with good interface quality between LFP and MWCNTs has been prepared using phytic acid. The MWCNTs wrap around the LiFePO4 particles to form a 3D network. The 3D network increases conductivity and the electron and ion transport.